Low Serum Allopregnanolone Is Associated with Symptoms of Depression in Late Pregnancy - Hellgren, Charlotte; Åkerud, Helena; Skalkidou, Alkistis; Bäckström, Torbjörn; Sundström-Poromaa, Inger (Neuropsychobiology, 2014)
Background: Allopregnanolone (3α-hydroxy-5α-pregnan-20-one) is a neurosteroid which has an inhibitory function through interaction with the GABA A receptor. This progesterone metabolite has strong sedative and anxiolytic properties, and low endogenous levels have been associated with depressed mood. This study aimed to investigate whether the very high serum allopregnanolone levels in late pregnancy covary with concurrent self-rated symptoms of depression and anxiety. Methods: Ninety-six women in pregnancy weeks 37-40 rated symptoms of depression and anxiety with the Montgomery-Åsberg Depression Rating Scale (MADRS-S) and Spielberger State-Trait Anxiety Inventory. Their serum allopregnanolone was analyzed by Celite chromatography and radioimmunoassay. Results: Ten women had elevated depression scores (MADRS-S ≥13), and this group had significantly lower allopregnanolone levels compared to women with MADRS-S scores in the normal range (39.0 ± 17.9 vs. 54.6 ± 18.7 nmol/l, p = 0.014). A significant negative correlation was found between self-rated depression scores and allopregnanolone concentrations (Pearson's correlation coefficient = -0.220, p = 0.031). The linear association between self-rated depression scores and allopregnanolone serum concentrations remained significant when adjusted for gestational length, progesterone levels, and parity. Self-rated anxiety, however, was not associated with allopregnanolone serum concentrations during pregnancy. Conclusion: High allopregnanolone serum concentrations may protect against depressed mood during pregnancy.